Detection of high levels of recombination generated during PCR amplification of RNA templates. (April 2006) - Yu, Wayne; Rusterholtz, Karl J.; Krummel, Amber T.; Lehman, Niles
Recombination during the PCR amplification of DNA templates can be a serious problem for those seeking to genotype heterogeneous populations, yet a boon to those seeking to enhance variation during in vitro evolution. Here, the extent to which PCR generates chimeric full-length products was estimated using a powerful restriction fragment-length polymorphism (RFLP) assay involving the use of fluorescently labeled PCR primers. Three different RNA-encoding DNA templates were assayed: (i)one for a group I ribozyme, (ii)one for a 16S ribosomal RNA (rRNA), and (iii)one for a messenger RNA (mRNA). In all cases, the observed frequency of chimeric PCR products exceeded 20%, and longer templates appear to produce more chimeric products. Although two of these templates have the potential to form secondary structures during the PCR, this tendency does not seem to heighten recombination frequency. These results corroborate previous studies that show that the production of chimeras can be best attenuated to a certain extent by varying the extension times in PCR.